FAMILY'S CONSEQUENCES OF BEING JOURNALIST IN A MIGHTY HEART MOVIE (2007) DIRECTED BY MICHAEL WINTERBOTTOM: A SOCIOLOGICAL APPROACH - AYU., AGUSTINA PANCA (2011)
This research paper elaborates Family's consequences of being journalist in A Mighty Heart movie that are analyzed through in sociological approach. The objectives of the research are to analyze the structural elements of the movie and to analyze the movie based on sociological approach. This research belongs to a descriptive qualitative research. The data of the research is the movie entitled A Mighty Heart whereas the data source comes from both primary data source related to the research as some books of sociological theories, movie script, internet and other relevant information. Having analyzed the movie, the researcher comes to the conclusions as follows: Michael Winterbottom presents the main character of Danny and Mariane Pearl that is drawn as a couple who works as a journalist in conflict area of Pakistan as parts of investigating in their jobs. During the flow of the story, Mariane becomes a widow because her husband is dead and killed by a militant group of Pakistan.